2021
DOI: 10.1016/j.socscimed.2021.113671
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the intersection between health emergencies and abortion during Zika in Brazil, El Salvador and Colombia

Abstract: The Zika outbreak of 2015-7 is a lens to analyse the positioning of abortion within in global health security. The sequelae of the virus almost exclusively affected newborn children, manifested through Congenital Zika Syndrome (CZS), and a focus on women at risk of, planning or being pregnant. At the global level, debate considered whether Zika would provide impetus for regulatory change for reproductive rights in Latin America, a region with some of the most restrictive abortion regulation in the world. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…This reflects the UK government's position that an effective response to COVID is reliant on individual responsibility, rather than social and structural barriers. What is so disappointing is that this narrow frame has already been shown to neglect the socio-economic consequences of outbreaks, particularly those affecting women [47,48]. Indeed, a parliamentary review of SAGE convened for the 2014-16 West Africa Ebola outbreak reported that 'many of our witnesses emphasised that … ensuring that the membership of SAGE included social scientists, were [sic] extremely important in controlling [the] outbreak' but did not mention their importance in understanding and mitigating the harmful downstream impacts of public health interventions [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects the UK government's position that an effective response to COVID is reliant on individual responsibility, rather than social and structural barriers. What is so disappointing is that this narrow frame has already been shown to neglect the socio-economic consequences of outbreaks, particularly those affecting women [47,48]. Indeed, a parliamentary review of SAGE convened for the 2014-16 West Africa Ebola outbreak reported that 'many of our witnesses emphasised that … ensuring that the membership of SAGE included social scientists, were [sic] extremely important in controlling [the] outbreak' but did not mention their importance in understanding and mitigating the harmful downstream impacts of public health interventions [49].…”
Section: Discussionmentioning
confidence: 99%
“…While being inconsistent in regard to the risk of COVID-19 infections to the professions discussed above, SAGE has consistently acknowledged that some sectors pose a greater risk of COVID-19 infection. These are meat packing, fish processing, supermarkets [48], events and hospitality [52], recreation and arts [53], close personal services [57], health and social care [59], and transport and emergency services [69]. Alongside this, SAGE also identified other characteristics of employment that may expose individuals to greater risk: inability to work at home, self-employed, on zero-hours contracts, high contact occupations, low pay, and ineligibility for statutory sick pay [37,38,39,57].…”
Section: Employment Sectorsmentioning
confidence: 99%
“…Structural gender inequities in Central and South America are well documented, and women often are not in control of their reproductive decisions [ 17 ]. Populations most affected by ZIKV often had limited access to reproductive health services, such as antenatal care, contraception counselling, and services -including emergency contraception-, safe abortion, and post-abortion care [ 28 , 29 ]. Many countries affected by ZIKV still have restrictive abortion laws, making safe abortion completely illegal or very difficult to access [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Populations most affected by ZIKV often had limited access to reproductive health services, such as antenatal care, contraception counselling, and services -including emergency contraception-, safe abortion, and post-abortion care [ 28 , 29 ]. Many countries affected by ZIKV still have restrictive abortion laws, making safe abortion completely illegal or very difficult to access [ 29 ]. Furthermore, the epidemic did not change the voluntary abortion landscape in any relevant way.…”
Section: Introductionmentioning
confidence: 99%
“…However, little has been investigated about the gender effect and the need to employ tailored solutions for women. A number of papers report experiences about women's health, including abortion (Vázquez-Quesada et al, 2020;Wenham et al, 2021), diabetes (Amgarth-duff et al, 2019), and oncology (Bednarova et al, 2020;Miceli et al, 2019). Some early studies conducted before the pandemic stressed that women seem to engage more with online and e-health tools than male patients (Escoffery, 2018;Reed et al, 2020).…”
Section: Female Patients and Female Workers During The Covid-19 Pandemicmentioning
confidence: 99%